Epigenetic Regulation of Angiogenesis in Development and Tumors Progression: Potential Implications for Cancer Treatment - Aspriţoiu, Veronica Mãdãlina; Stoica, Ileana; Bleotu, Coralia; Diaconu, Carmen Cristina (Frontiers in Cell and Developmental Biology, 2021)
Angiogenesis is a multi-stage process of new blood vessel development from pre-existing vessels toward an angiogenic stimulus. The process is essential for tissue maintenance and homeostasis during embryonic development and adult life as well as tumor growth. While in normal conditions, angiogenesis is involved in physiological processes, such as wound healing, cyclic regeneration of the endometrium, placental development and repairing certain cardiac damage, in pathological conditions, it is associated with cancer development and metastasis. The regulatory mechanisms of angiogenesis in carcinogenesis are tightly controlled at genetic and epigenetic levels. While genetic alterations are the critical part of gene silencing in cancer cells, the epigenetic deregulations can lead to repression of tumor suppressor genes or oncogenes' activation, becoming an important event in early development and the late stages of tumor development, as well. Actually, the global alteration of the epigenetic spectrum, which involve DNA methylation, histone modifiers and readers, chromatin remodelers, microRNAs, and other components of chromatin, is considered one of the hallmarks of cancer, and the efforts are concentrated on the discovery of molecular epigenetic markers that identify precursor lesions or cancer at its earliest stage. This review aims to highlight the recent findings on genetic and epigenetic changes that can occur in physiological and pathological angiogenesis and analyze current knowledge on how deregulation of epigenetic modifiers contributes to tumorigenesis and tumour maintenance. Also, we will evaluate the clinical relevance of epigenetic markers of angiogenesis and the potential use of "epi-drugs" in modulating the sensitivity of cancer cells to anticancer therapy, including chemotherapy, radiation therapy, hormone therapy and immunotherapy as anti‐angiogenic strategies in cancer.